2019
DOI: 10.1021/acs.jmedchem.8b01860
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Pt(IV) Bifunctional Prodrug Containing 2-(2-Propynyl)octanoato Axial Ligand: Induction of Immunogenic Cell Death on Colon Cancer

Abstract: The synthesis, characterization, and in vitro activity of a cyclohexane-1R,2R-diamine-based Pt(IV) derivative containing the histone deacetylase inhibitor rac-2-(2-propynyl)octanoato, namely, (OC-6-44)-acetatodichlorido(cyclohexane-1R,2R-diamine)-(rac-2-(2-propynyl)octanoato)platinum(IV), are reported together with those of its isomers containing enantiomerically enriched axial ligands. These Pt(IV) complexes showed comparable activity, of 2 orders of magnitude higher than reference drug oxaliplatin on three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 74 publications
0
43
0
4
Order By: Relevance
“…Despite increasing interest in the possible associations between oxoplatin and other drugs [ 41 , 42 , 43 , 44 , 45 , 46 ], there is currently no recommended approach to systematically improving the anti-cancer activity of bifunctional drugs based on Pt(IV). With the aim of contributing to the design of enhanced anti-cancer drugs, we used a state-of-the-art computational approach to screen the latest FDA-approved oncology drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increasing interest in the possible associations between oxoplatin and other drugs [ 41 , 42 , 43 , 44 , 45 , 46 ], there is currently no recommended approach to systematically improving the anti-cancer activity of bifunctional drugs based on Pt(IV). With the aim of contributing to the design of enhanced anti-cancer drugs, we used a state-of-the-art computational approach to screen the latest FDA-approved oncology drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, Pt drugs induce cancer cell death by interfering with DNA synthesis or causing chemical damage to DNA, which is mainly manifested by apoptosis. However, accumulating evidences indicate that Pt drugs may have other molecular targets in addition to DNA, which can induce cell death through non-apoptotic pathways, such as autophagy, necrosis, and even immunogenicity [105,[120][121][122][123]. Complexes 44-46 ( Figure 16) showed a dose-dependent antiproliferative activity in the A2780 cells, with the cytotoxicity order of 44 < 45 < 46, by a combinative apoptotic mechanism involving mitochondrial and autophagic pathways [124].…”
Section: Miscellaneous Monofunctinoal Pt II Complexesmentioning
confidence: 99%
“…Sabbatini et al. found that a Pt IV prodrug containing a 2‐(2‐propyl) octanol axial ligand‐induced ICD in colon cancer [27] . Kaur et al.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Sabbatini et al found that aPt IV prodrug containing a2-(2-propyl) octanol axial ligandinduced ICD in colon cancer. [27] Kaur et al reported acopper-(II) complex containing apolypyridyl ligand and aSchiff base ligand had the capable of inducing ICD in breast cancer stem cells. [28] Ding et al proved MnOx Nanospikes induced ICD by chemodynamic therapy (CDT) and ferroptosis.…”
Section: Introductionmentioning
confidence: 99%